2017
DOI: 10.1021/acsnano.6b06796
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Targeted Surface-Enhanced Resonance Raman Scattering Nanoprobe Ratiometry for Detection of Microscopic Ovarian Cancer

Abstract: Ovarian cancer has a unique pattern of metastatic spread, in that it initially spreads locally within the peritoneal cavity. This is in contrast to most other cancer types, which metastasize early on via the blood stream to distant sites. This unique behavior opens up an opportunity for local application of both therapeutic and imaging agents. Upon initial diagnosis, 75% of patients already present with diffuse peritoneal spread involving abdominal organs. Complete resection of all tumor implants has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
129
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 28 publications
1
129
0
Order By: Relevance
“…Nanostars and nanorods accumulate the electromagnetic field at their tips, giving rise to very strong single particle SERS intensities (Alvarez-Puebla et al 2010). Similar approaches as for spherical colloids were applied for the preparation of SEPs using Au nanostars functionalized with thiolated PEG (Morla-Folch et al 2014;Yuan et al 2012), or coated with silica shells (Andreou et al 2016;Henry et al 2016;Huang et al 2016;Mir-Simon et al 2015;Oseledchyk et al 2017). Figure 2d, h shows Au nanostars coated with Ag and silica, respectively.…”
Section: Surface-enhanced Raman Scattering Encoded Particlesmentioning
confidence: 99%
See 4 more Smart Citations
“…Nanostars and nanorods accumulate the electromagnetic field at their tips, giving rise to very strong single particle SERS intensities (Alvarez-Puebla et al 2010). Similar approaches as for spherical colloids were applied for the preparation of SEPs using Au nanostars functionalized with thiolated PEG (Morla-Folch et al 2014;Yuan et al 2012), or coated with silica shells (Andreou et al 2016;Henry et al 2016;Huang et al 2016;Mir-Simon et al 2015;Oseledchyk et al 2017). Figure 2d, h shows Au nanostars coated with Ag and silica, respectively.…”
Section: Surface-enhanced Raman Scattering Encoded Particlesmentioning
confidence: 99%
“…In fact, it has been demonstrated that SEPs can adhere to tumor tissues in less than minutes, although the nonspecifically adsorbed SEPs must be removed by washing the tissue with serum (Wang et al 2014a). The obstacle set by the high background distribution of non-specifically bound nanoparticles can be overcome by implementing ratiometric approaches where one of the SEP type in the particle cocktail is used as a nonspecific internal reference to visually enhance the preferential adhesion of other targeting nanoparticles on tumor tissues (Mallia et al 2015;Oseledchyk et al 2017;Pallaoro et al 2011). Implementation of these methods is rather straightforward for SERS imaging due to the high degree of multiplexing provided by the narrow Raman linewidths.…”
Section: Sep Characterization Of Tumor Tissuesmentioning
confidence: 99%
See 3 more Smart Citations